Respuesta :
l = longer piece s = shorter piece
{ l + s = 63
{ l = s + 15
l + s = 63
(s + 15) + s = 63
2s = 63 - 15
2s = 48
s = 48
2
s = 24
l + s = 63
l + 24 = 63
l = 63 - 24
l = 39
S = 39 cm
hope this helps
Plz mark me as brainlest
{ l + s = 63
{ l = s + 15
l + s = 63
(s + 15) + s = 63
2s = 63 - 15
2s = 48
s = 48
2
s = 24
l + s = 63
l + 24 = 63
l = 63 - 24
l = 39
S = 39 cm
hope this helps
Plz mark me as brainlest
if longer piece is x cm long the shorter will be x - 15 cm long
so we have
x + x - 15 = 63
2x = 63+15 = 78
x = 78/2 = 39
longer piece is 39 cms long
so we have
x + x - 15 = 63
2x = 63+15 = 78
x = 78/2 = 39
longer piece is 39 cms long